STUDI PENGARUH KUALITAS PRODUK DAN PELAYANAN TERHADAP LOYALITAS PELANGGAN: KASUS FAMILY MART DI KALANGAN MAHASISWA UNIVERSITAS AIRLANGGA - Wanda Fauziyah Rahmah; Ahmad Afif Augusta; Tyas Sonya Ratri (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2024)
The company's capability to deliver superior products and services plays a crucial role in building customer loyalty. Both contribute to building trust, and customer satisfaction, creating positive experiences, and strengthening customer and company relationships, to encourage long-term loyalty. The purpose of the study was to study how Family Mart's product and service quality affects customer loyalty among Airlangga University students. In this study, a quantitative approach was used together with a survey. Data were collected through questionnaires randomly selected from 150 Family Mart customers of Airlangga University. To determine how much influence the two independent variables have on the dependent variable, data analysis was carried out using the multiple linear regression method. Data was processed using the SPSS program. The results showed that customer loyalty (Y) was significantly influenced by the product quality variable (X1). In the calculation of the t-test of the product quality variable (X1), it created a value of 6,980 > 1,976 so that its validity can be recognized. While the service quality variable (X2) gave significant results on customer loyalty (Y) with a t-value of 6,980> 1,976. Both variables simultaneously have a positive and significant effect on customer loyalty (Y) with a calculated F value > from F table, 129.810 > 3.06. So the quality of Family Mart products and services simultaneously has a positive and significant impact on customer loyalty among Airlangga University students.